THE COMPARISONS AND CONTRASTS BETWEEN ENGLISH AND MALAY LANGUAGES - Mohd Nazri Latiff Azmi; Lidwina Teo Pik Ching; Norbahyah Binti Jamaludin; Muhammad Nur Haziq Bin Ramli; Muhammad Habibbullah Bin Razali; Muhammad Ammar Yasser Bin Amram; Kauselya A/P Jayakumar (English Review: Journal of English Education, 2016)
English and Malay languages are categorized as popular languages in the world.Â  However, both languages underwent different history and composition. This study investigates the languages in terms of history, phonology, loanwords, grammar, morphology and semantics. The purposes of studying the comparisons and contrasts of both languages are not only to analyze the uniqueness of the languages but also to identify the process of understanding the languages especially the view of second language learners. It is found that two languages come from different background; somehow they share similar characteristics such as the vowels sounds, loanwords and semantics. However, the learners face difficulty in learning both languages especially in pronunciations and spelling.Keywords: English language, Malay language, history of language